2008
DOI: 10.1097/ico.0b013e31815873c7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Loteprednol/Tobramycin Versus Dexamethasone/Tobramycin on Intraocular Pressure in Healthy Volunteers

Abstract: Loteprednol/tobramycin was significantly less likely to produce elevations in IOP than was dexamethasone/tobramycin in healthy subjects treated for 28 days. Both loteprednol etabonate/tobramycin and dexamethasone/tobramycin were well tolerated with low risks for systemic AEs and ocular AEs other than elevation in IOP for dexamethasone/tobramycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 29 publications
3
40
0
2
Order By: Relevance
“…35,36 Previous studies have confirmed the relatively lower risk of IOP elevation with LE compared with other ocular steroids, including studies in known steroid responders. [37][38][39][40][41][42][43][44][45] Limitations of this analysis included the lack of either a non-active control, or a control of a different drug category and the 2-week follow-up period. The study treatments both contained the same antibacterial (tobramycin), and a highly effective corticosteroid (loteprednol etabonate or dexamethasone).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Previous studies have confirmed the relatively lower risk of IOP elevation with LE compared with other ocular steroids, including studies in known steroid responders. [37][38][39][40][41][42][43][44][45] Limitations of this analysis included the lack of either a non-active control, or a control of a different drug category and the 2-week follow-up period. The study treatments both contained the same antibacterial (tobramycin), and a highly effective corticosteroid (loteprednol etabonate or dexamethasone).…”
Section: Discussionmentioning
confidence: 99%
“…Основными побочными эффектами длительно-го применения стероидов местно являются прогрес-сирование катаракты, повышение внутриглазного давления, замедление процессов репарации после-операционных ран, увеличение риска развития ин-фекционных кератитов [54].…”
Section: лечениеunclassified
“…3) Specifically, LE is the 17b-chloromethyl ester of D1-cortienic acid etabonate, a derivative of the prednisolone metabolite D1-cortienic acid. This allows LE to be active at its site of action and subsequently undergo predictable hydrolysis to inactive carboxylic acid metabolites by naturally occurring ocular esterases, resulting in reduced side-effects of elevated IOP (Table 3) (Armaly 1965;Mindel et al 1980;Manabe et al 1984;Bartlett et al 1993a;Urban & Dreyer 1993;Leibowitz et al 1996;Ilyas et al 2004;Bodor & Buchwald 2005;Holland et al 2008;White et al 2008;Holland et al 2009). In addition, the C-20 ketone group on corticosteroids is associated with the formation of cataracts through the development of Schiff base intermediates via an interaction between the C-20 ketone group and lysine residues of proteins (Manabe et al 1984;Bodor & Buchwald 2005).…”
Section: ; Bielory 2008mentioning
confidence: 99%